Contrasting effects of aquatic subsidies on a terrestrial trophic cascade. (24th May 2017) - Graf, Nadin; Bucher, Roman; Schäfer, Ralf B.; Entling, Martin H.
Abstract : Subsidies from adjacent ecosystems can alter recipient food webs and ecosystem functions, such as herbivory. Emerging aquatic insects from streams can be an important prey in the riparian zone. Such aquatic subsidies can enhance predator abundances or cause predators to switch prey, depending on the herbivores. This can lead to an increase or decrease of in situ herbivores and herbivory. We examined the effects of aquatic subsidies on a simplified terrestrial food web consisting of two types of herbivores, plants and predators (spiders). In our six-week experiment, we focused on the prey choice of the spiders by excluding predator immigration and reproduction. In accordance with predator switching, survival of leafhoppers increased in the presence of aquatic subsidies. By contrast, the presence of aquatic subsidies indirectly reduced weevils and herbivory. Our study shows that effects of aquatic subsidies on terrestrial predators can propagate through the food web in contrasting ways. Thereby, the outcome of the trophic cascade is determined by the prey choice of predators.